Design of Oceanarium in Banda aceh - monika razifanur razifanur (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
Lack of tourist place in Banda Aceh and a variety of natural potential that can be developed, one of which is the beauty of underwater parks and marine life in Indonesia. planning to make Oceanarium objects in Banda Aceh City become one of the objects needed in terms of developing tourism needs (exhibition) and becoming a center of learning (education) and maintaining underwater conservation (conservation). Site selection is in Ulee Lheue, Banda Aceh. And the theme applied in this design object is the Metaphor Architecture. The tourism potential is increasingly developing in a positive direction and is very beneficial for the tourism industry. which is felt to be very suitable to the needs of Oceanarium design in the city of Banda Aceh. Therefore, the design of this Oceanarium is needed to facilitate existing activities and can increase the country's foreign exchange profits, especially in the tourism sector.